Executive Summary: Project for the Use of Water Resources in the Guayas River Basin - Calle Eguiguren, Emilio (Revista Universidad de Guayaquil, 2008)
The Technology Transfer and Development Centers -CTT's were created by law in 1999 under the assumption that there was a high potential for a productive relationship of mutual benefit between the university and the productive sector, but that there was no mechanism for this relationship to become concrete and grow over time.A little more than 8 years have passed since the enactment of this Law, and the fact is that the private productive sector is only marginally interested in working with universities. In fact, there are very few relevant cases in which the University has participated.
Keywords: CTT’s; Hydro